Non-restrictive relative clauses in Construction Based HPSG - Arnold, Doug (Proceedings of the 11th International Conference on Head-Driven Phrase Structure Grammar, 2004)
This paper presents an account of English non-restrictive (ˋappositive') relativeclauses (NRCs) in the framework of ˋconstruction based' HPSG.Specifically, it shows how the account of restrictive relative clauseconstructions presented in Sag (1997) can be extended to provide an account of thesyntax and semantics of NRCsand of the main differences between NRCs and restrictive relatives.The analysis reconciles the semantic intuition thatNRCs behave like independent clauses with their subordinate syntax. A significantpoint is that, in contrast with many other approaches, it employs only existing,independently motivated theoretical apparatus, and requires absolutely no newstructures, features, or types.